Structural determinants of food insufficiency, low dietary diversity and BMI: a cross-sectional study of HIV-infected and HIV-negative Rwandan women. Issue 2 (13th April 2012) - Sirotin, Nicole; Hoover, Donald; Segal-Isaacson, C J; Shi, Qiuhu; Adedimeji, Adebola; Mutimura, Eugene; Cohen, Mardge; Anastos, Kathryn
Abstract : Objectives: In Sub-Saharan Africa, the overlapping epidemics of undernutrition and HIV infection affect over 200 and 23 million people, respectively, and little is known about the combined prevalence and nutritional effects. The authors sought to determine which structural factors are associated with food insufficiency, low dietary diversity and low body mass index (BMI) in HIV-negative and HIV-infected Sub-Saharan women. Study design: Cross-sectional analysis of a longitudinal cohort. Setting: Community-based women's organisations. Participants: 161 HIV-negative and 514 HIV-infected Rwandan women. Primary and secondary outcome measures: Primary outcomes included food insufficiency (reporting 'usually not' or 'never' to 'Do you have enough food?'), low household dietary diversity (Household Dietary Diversity Score ≤3) and BMI <18.5 (kg/m 2 ). The authors also measured structural and behavioural factors including: income, household size, literacy and alcohol use. Results: Food insufficiency was prevalent (46%) as was low dietary diversity (43%) and low BMI (15%). Food insufficiency and dietary diversity were associated with low income (adjusted odds ratio (aOR)=2.14 (95% CI 1.30 to 3.52) p<0.01), (aOR=6.51 (95% CI 3.66 to 11.57) p<0.001), respectfully and illiteracy (aOR=2.00 (95% CI 1.31 to 3.04) p<0.01), (aOR=2.10 (95% CI 1.37 to 3.23) p<0.001), respectfully and were not associated with HIV infection. Alcohol use was strongly associated with food insufficiency (aOR=3.23 (95% CI 1.99 to 5.24) p<0.001). Low BMI was inversely associated with HIV infection (aOR≈0.5) and was not correlated with food insufficiency or dietary diversity. Conclusions: Rwandan women experienced high rates of food insufficiency and low dietary diversity. Extreme poverty, illiteracy and alcohol use, not HIV infection alone, may contribute to food insufficiency in Rwandan women. Food insufficiency, dietary diversity and low BMI do not correlate with one another; therefore, low BMI may not be an adequate screening tool for food insufficiency. Further studies are needed to understand the health effects of not having enough food, low food diversity and low weight in both HIV-negative and HIV-infected women.